Study on the Mechanical Response of FSP-IV Steel Sheet Pile Cofferdam and the Collaborative Mechanism of Sediment Control Technology in the Nenjiang Water Intake Project - Ziguang Zhang; Liang Wu; Rui Luo; Lin Wei; Feifei Chen (Buildings)
In response to the dual challenges of the mechanical behavior of steel sheet pile cofferdam and sediment control in urban water intake projects, a multi-method integrated study was conducted based on the Nenjiang Project. The results show that the peak stress of FSP-IV steel sheet piles (64.3 MPa) is located at a depth of 5.5–8.0 m in the center of the foundation pit, and that the maximum horizontal displacement (6.96 mm) occurs at the middle of the side span of the F pile. The internal support stress increases with depth, reaching 87.2 MPa at the bottom, with significant stress concentration at the connection of the surrounding girder. The lack of support or excessively large spacing leads to insufficient stiffness at the side span (5.3 mm displacement at the F point) and right-angle area (B/H point). The simultaneously developed sediment control integrated system, through double-line water intake, layered placement of the geotextile filter, and the collaborative construction of the water intake hole–filter layer system, achieves a 75% reduction in sediment content and a decrease in standard deviation. This approach ensures stable water quality and continuous water supply, ultimately forming a systematic solution for water intake in high-sediment rivers.